Assessment of Level of Service on Freeways by Microscopic Traffic Simulation. Issue 1 (January 2014) - Geistefeldt, Justin; Giuliani, Stefan; Vortisch, Peter; Leyn, Ulrike; Trapp, Roland; Busch, Fritz; Rascher, Andrea; Celikkaya, Nihan
Analytical methods for the assessment of traffic flow quality on freeways are valid for standard types of basic, merge, diverge, and weaving segments. For more complex freeway facilities, microscopic traffic flow simulation is widely used. In this case, the definition and the computation of the level of service must be compatible with the analytical methods. For the forthcoming edition of the German Highway Capacity Manual, standards and user guidance for the application of microscopic traffic flow simulation tools for quality of service assessment on freeways were developed. For typical freeway segments, standard parameter sets for the simulation tools VISSIM, AIMSUN, PARAMICS, BABSIM, and Simulation of Urban Mobility were developed. This study applied these simulation tools for a diverge with a two-lane exit ramp. The results show that the simulation results represent the manual's design capacities well.